A guide to pollen morphology of some Malaysian mangrove plants - Ibrahim, Faridah Hanum; Guvensen, A.; Ozturk, Munir (Universiti Putra Malaysia Press, 2017)
A Guide to Pollen Morphology of Some Malaysian Mangrove Plants is a quick reference for those seeking information on the pollen of mangrove plants. Pollen examined by the Scanning Electron Microscope (SEM) details the characters of pollen at high accuracy and magnification such as ornamentation, aperture, lumen and shape which are important to a certain extent in differentiating plant taxa at the species, genus or family level. Pictures of the plant in the field are also included for reference.